Common Fixed Point Results on Complex Valued G_b-Metric Spaces: Ozgur Ege1, Ismet Karaca - Team, Support (Thai Journal of Mathematics, 2018)
In this study, we introduce some notions such as coincidence point, compatible and occasionally weakly compatible maps in complex valued Gb-metric spaces. Then using these notions we prove some new common fixed point theorems in complex valued Gb-metric spaces.